Building the Capacity of Local Government to Scale Up Community-Led Total Sanitation and Sanitation Marketing in Rural Areas - Rosensweig, Fred; Kopitopoulos, Derko (World Bank, Washington, DC, 2014)
The World Bank administered Water and Sanitation Program (WSP) recently passed the mid-point of the four-year timeframe for its Global Scaling up Sanitation Project (TSSM). TSSM tests proven and promising Community-Led Total Sanitation (CLTS) approaches to create community-wide demand for stopping open defecation and improving sanitation. It is coupled with the use of sanitation marketing techniques to further strengthen the demand for sanitation at the household level and improve the supply of affordable sanitation-related goods and services produced by the local private sector for the rural poor. The report reviews the role of local government in these areas in the context of the management models that TSSM is using in all three countries. While there are variations in the models that reflect the country contexts, all three countries have placed local governments at the center of the implementation arrangements. In all three countries, the roles and responsibilities of the districts are carried out at three levels of local government, district, sub-district, and village. The study concludes that the model of working through local governments with the support of resource agencies, national or regional non- governmental organizations (NGOs), to build the capacity of local government, is fundamentally sound.